Hereditary breast cancer: genetic and clinical hetergeneity, genetic testing, prophylactic surgery - L. N. Lyubchenko; Ye. I. Bateneva; I. K. Vorotnikov; S. M. Portnoy; O. V. Krokhina; V. A. Sobolevskiy; L. G. Zhukova; V. A. Khaylenko; S. A. Tyulyandin (Успехи молекулярной онкологии, 2015)
5–10 % of breast cancer cases are hereditary, 30 % of them are caused by BRCA1 and BRCA2 mutations (breast / ovarian cancer syndrome). Average cumulative risks of breast and ovarian cancer in BRCA1 mutation carriers run up to 87 % and 44 %, correspondingly. The risk for contralateral breast cancer is also high: after 25 years, 62.9 % of patients with BRCA1 mutation who were younger than 40 years of age at first breast cancer develop contralateral breast cancer. The role of single nucleotide polymorphisms in BRCA1 and BRCA2 genes modifying breast and gynaecological cancer risks is actively studied. Genetic testing is performed as a part of genetic counselling. The main inclusion criteria are multiple affected family members with breast / ovarian cancer, breast cancer at young age (under 35–50 years), ovarian cancer at any age, male breast cancer, morphological features of breast cancer (triple-negative, medullar tumors), ethnicity (Jewish ancestry). High-risk individuals carrying BRCA mutations undergo specific surveillance, chemoprophylaxis and surgery protocols. Prophylactic bilateral mastectomy reduces breast cancer risk by 90–94 %.